2014
DOI: 10.1111/epi.12503
|View full text |Cite
|
Sign up to set email alerts
|

Screening of major depression in epilepsy: The Neurologic Depression Disorders Inventory in Epilepsy‐Spanish version (Argentina)

Abstract: SUMMARYObjectives: To validate and translate the English version of the Neurologic Depression Disorders Inventory in Epilepsy (NDDI-E) into Spanish as a screening instrument for major depressive episodes (MDE) for patients with epilepsy from Argentina and Uruguay. Methods: One hundred fifty-five consecutive outpatients with epilepsy participated in this study. The module of MDE of the MINI International Neuropsychiatric Instrument (MINI Plus version) was used as the gold standard against which the translated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…All studies included male and female participants, and sample sizes ranged from 44 to 575 (median 143). Twenty‐seven studies examined participants ≥18 years old, seven studies >16 years old, and only one study examined youth (10–17 years old) . In three studies it was inferred from the reported mean and median ages that these participants were adults .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies included male and female participants, and sample sizes ranged from 44 to 575 (median 143). Twenty‐seven studies examined participants ≥18 years old, seven studies >16 years old, and only one study examined youth (10–17 years old) . In three studies it was inferred from the reported mean and median ages that these participants were adults .…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly validated screening tools were the NDDI‐E (n = 26 validations), Beck Depression Inventory (BDI; n = 12 validations, including the modified BDI, BDI‐Fast Screen, BDI‐I, BDI‐II, and the Cognitive Affective Subscale for the BDI), Hospital Anxiety and Depression Scale (HADS; n = 10 validations, including the HADS total score, HADS‐Depression [HADS‐D] Score, and one study used the HADS‐Anxiety [HADS‐A] score to assess depression), Emotional Thermometers (ETs; n = 5 validations, including the ET7, ET4, and individual questions on anxiety and depression), Patient Health Questionnaire 9 (PHQ‐9; n = 4 validations), Patient Health Questionnaire 2 (PHQ‐2; n = 2 validations), and the Hamilton Rating Scale for Depression (HAM‐D or HRSD; n = 4 validations, including the HRSD 17 and 21 question versions). The NDDI‐E was validated in 13 languages including Arabic, Chinese, Danish, English, French, German, Greek, Italian, Japanese, Korean, Portuguese, Spanish, and Serbian …”
Section: Resultsmentioning
confidence: 99%
“…In the original version, the score above 15 points has a high predictive value for major depression (Gilliam et al, 2006). The NDDI-E has been translated from English into other languages and approved as a tool for the diagnosis of depression in PWEs in Argentina (Thomson et al, 2014), Brazil (De Oliveira et al, 2010, Italy (Mula et al, 2012), China (Guo et al, 2015), France (Micoulaud-Franchi et al, 2015), Spain (Di Capua et al, 2012), Korea (Ko et al, 2012), Japan (Tadokoro et al, 2012), Germany (Metternich et al, 2012) and Greece (Zis et al, 2013). The aim of this study was to validate the Polish version of the NDDI-E scale.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the work of Thomson et al., 2 who translated and validated the NDDI‐E into Spanish for patients in Argentina and Uruguay. Despite the already validated version of NDDI‐E in Spanish for patients in Spain, 3 Thomson et al 2 .…”
mentioning
confidence: 99%
“…We read with great interest the work of Thomson et al., 2 who translated and validated the NDDI‐E into Spanish for patients in Argentina and Uruguay. Despite the already validated version of NDDI‐E in Spanish for patients in Spain, 3 Thomson et al 2 . acknowledged the significant differences in the vocabulary, idioms, and local expressions between the Spanish‐speaking countries, and consequently made a second version of the Spanish NDDI‐E.…”
mentioning
confidence: 99%